Disentangling the Role of Deviant Letter Position on Cognate Word Processing - Comesaña, Montserrat; Haro, Juan; Macizo, Pedro; Ferré, Pilar (Frontiers in Psychology, 2021)
The way letter position is coded has been extensively assessed during the recognition of native words leading to the development of a new generation of models that assume more flexible letter position coding schemes than classical computational models such as the Interactive Activation (IA) model (McClelland & Rumelhart, 1981). However, whether similar letter-position encoding mechanisms occur during second language word recognition has been largely less explored despite its implications for the leading model of bilingual word recognition (Multilink, Dijkstra et al., 2019) since it assumes the input coding scheme of the IA model. In this study, we aimed to examine this issue through the manipulation of the position of the deviant letter of cognate words (outer and internal letters). Two experiments were conducted with Catalan-Spanish bilinguals (a masked priming lexical decision task and a 2 alternative forced-choice task) and their respective monolingual controls. The results revealed a differential processing for the first letter in comparison to the others as well as modulations as a function of language cue, suggesting amendments to the input-coding scheme of the Multilink model.